2022
DOI: 10.3390/su141811260
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Optimization of Tourist-Oriented Villages by Space Syntax Based on Population Analysis

Abstract: Tourism-oriented countryside is a development object that cannot be ignored in Chinese rural revitalization. As a special type of countryside, urban expansion and development have led to the gradual reduction of rural areas, which, in turn, has led to the deterioration of the spatial structure of tourism villages and the interdependence between villagers, merchants, and tourists. This has caused the loss of vitality of rural tourism spaces and the hollowing out of tourism villages. In our study, we used Space … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…A notable example is the spatial syntax approach [5,6], widely used these days [4] in multidisciplinary studies [7][8][9][10][11], which focuses on analysing the integration, intersection, and centrality of streets based on graphical analysis, determining its importance in the urban fabric. In the same line, it is possible to talk about the shortest routes and a street's straightness analysis used in walkability studies [12,13].…”
Section: Research Background 1urban Street Attributesmentioning
confidence: 99%
“…A notable example is the spatial syntax approach [5,6], widely used these days [4] in multidisciplinary studies [7][8][9][10][11], which focuses on analysing the integration, intersection, and centrality of streets based on graphical analysis, determining its importance in the urban fabric. In the same line, it is possible to talk about the shortest routes and a street's straightness analysis used in walkability studies [12,13].…”
Section: Research Background 1urban Street Attributesmentioning
confidence: 99%
“…Consequently, it provides a conducive environment for community organization, collectivity enhancement, idea exchange, and action implementation [77]. In terms of demographic shifts, the user group composition in tourist villages has transformed from a binary structure consisting of villagers and tourists to a tripartite one encompassing villagers, tourists, and traders [78]. Rural residents have been increasingly influenced by the influx of diverse tourist groups, seasonal visitors, and labor migrants.…”
Section: Mechanisms Of Publicness Idiosyncrasies In Rural Public Spacementioning
confidence: 99%
“…It is also worth mentioning that the concept of Spatial Syntax, initially developed by Hillier & Hanson [36], has garnered increasing relevance within these studies due to its versatility and applicability in multidisciplinary research [37]. To illustrate its integration Wang et al [38] and Xu et al [39] utilize Spatial Syntax methodologies and GIS to analyse urban spaces, offering valuable insights from a tourism perspective. So far, it has been observed that recreational carrying capacity studies have been well solved in closed and/or confined spaces, but it is always complex to approach large areas with traditional methods.…”
Section: Background and State Of The Artmentioning
confidence: 99%